Javan Rhino (Rhinoceros sondaicus Desmarest 1822) Utilization Distribution and Habitat Selection in Ujung Kulon National Park - Yanto Santosa; U Mamat Rahmat; Lilik Budi Prasetyo; Agus Priyono Kartono (Institut Pertanian Bogor (IPB University), 2013)
Javan rhino (Rhinoceros sondaicus Desmarest 1822) is one of world's rarest endangered species (IUCN 2008). Currently, their distribution is limited to Ujung Kulon National Park (UKNP) of Indonesia. Natural disasters, disease, poaching, encroachment, and competition are threats facing Javan rhino's population, hence creating pockets of habitats outside the UKNP was necessary and should be based on scientific studies of javan rhino utilization distribution and habitat selection in UKNP as the natural habitat. The objectives of the study were to determine the utilization distribution of Javan rhino and its habitat characteristics and determine javan rhino habitat selection within UKNP. The research indicated that Javan rhinos highest use of areas comprised of swampy shrub (w = 2.197) and shrub (w = 2.012), relatively open habitat (w = 4.233), flat area (w = 1.313) and slightly sloping areas (w = 1.007), lowland (w = 1.346), close to river (w = 1.087), close to road network (w = 1.395), close to coasts/beaches (w = 1.862), close to wallowing areas (w = 3.709), and close to rumpang (w = 3.783). The results suggested that javan rhino showed selection and preferences for its habitat.